2021
DOI: 10.2147/dddt.s314767
|View full text |Cite
|
Sign up to set email alerts
|

Bardoxolone-Methyl Prevents Oxidative Stress-Mediated Apoptosis and Extracellular Matrix Degradation in vitro and Alleviates Osteoarthritis in vivo

Abstract: Oxidative stress-induced chondrocyte apoptosis and extracellular matrix (ECM) degradation plays an important role in the progression of osteoarthritis (OA). Bardoxolone methyl (BM), a semisynthetic triterpenoid, exerts strong effect against oxidative stress. The purpose of the present study was to determine the effectiveness of bardoxolone-methyl (BM) in preventing oxidative stress-induced chondrocyte apoptosis and extracellular ECM degradation in vitro and the role of alleviating OA progression in vivo. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Karim et al found that iron overload in chondrocytes can induce oxidative stress, cell cycle arrest and apoptosis (Karim et al, 2022). Pang et al found that Bardoxolonemethyl can inhibit chondrocyte apoptosis and ECM degradation induced by oxidative stress in vitro, and reduce OA in vivo (Pang et al, 2021).…”
Section: How To Solve the Oxidative Stress In Knee Osteoarthritismentioning
confidence: 99%
“…Karim et al found that iron overload in chondrocytes can induce oxidative stress, cell cycle arrest and apoptosis (Karim et al, 2022). Pang et al found that Bardoxolonemethyl can inhibit chondrocyte apoptosis and ECM degradation induced by oxidative stress in vitro, and reduce OA in vivo (Pang et al, 2021).…”
Section: How To Solve the Oxidative Stress In Knee Osteoarthritismentioning
confidence: 99%
“…Senescent chondrocytes exhibit telomere shortening with age and the nonreplicative senescence of chondrocytes mainly induced by external or endogenous stress, such as reactive oxygen species (ROS) [ 6 ]. Previous studies have confirmed that extravagant levels of ROS could, in turn, aggravate senescence and set off pathological modifications of cellular proteins and lipids, thereby restraining chondrocyte activity and destroying ECM homeostasis, finally giving rise to damage of articular cartilage [ 7 , 8 ]. Thus, inhibition of chondrocyte oxidative stress is proposed as an effective remedy strategy for senile cartilage quality loss.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress can accelerate the process of IDD in many ways, including through apoptosis, ECM degeneration, senescence, and autophagy (Feng et al, 2017). Many reports have shown that BARD has a strong antioxidative effect (Khurana et al, 2020;Pang et al, 2021;Snijders et al, 2021). However, whether BARD can alleviate IVD degeneration caused by compression has not been studied.…”
Section: Discussionmentioning
confidence: 99%